Permasalahan Stunting dan Pencegahannya - Kinanti Rahmadhita (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The problem of short children (stunting) is one of the nutritional problems that are the focus of the Government of Indonesia, Stunting is nutritional status based on the PB / U or TB / U index wherein anthropometric standards for assessing children's nutritional status, the measurement results are at the threshold (Z -Score) <-2 SD to -3 SD (short) and <-3 SD (very short). Stunting that has occurred if not balanced with catch-up growth results in decreased growth, stunting problems are a public health problem associated with increased risk of morbidity, death, and obstacles to the motor and mental growth. Seeing the dangers posed by stunting, the Government of Indonesia is committed to addressing and reducing stunting prevalence, which was discussed through a limited meeting on stunting interventions held with the head of the National Team for the Acceleration of Poverty Reduction in 2017, that at the meeting discussed the need to strengthen coordination and expand coverage programs carried out by the relevant Ministries / Institutions (K / L), to improve the quality of the program in order to reduce the stunting rate in each region that has entered the priority village. And also to study the policy focus of the nutrition improvement movement aimed at the first 1000 days of life in a global order called Scaling Up Nutrition (SUN)